Aristotle’s Criticism of the Platonic Idea of the Good in Nicomachean Ethics 1.6 - Mouzala, Melina G. (Peitho. Examina Antiqua, 2017)
In Nicomachean Ethics 1.6, Aristotle directs his criticism not only against the Platonic Idea of the Good but also against the notion of a universal Good. In this paper, I also examine some of the most interesting aspects of his criticism of the Platonic Good and the universal Good in Eudemian Ethics 1.8. In the EN, after using a series of disputable ontological arguments, Aristotle’s criticism culminates in a strong ethical or rather practical and, simultaneously, epistemological argument, from which a dialectical postulatum emerges. This argument aims to show that we have to discover the dialectical stages or grades which constitute the relation between the ultimate End, i.e., the Good simpliciter or the absolute Good, and the relational goods till the last prakton good in which each specific praxis ends. According to the present reading, Aristotle sets out to establish a kind of Dialectic of the ends (Dialektikē tōn telōn) or Dialectic of the goods (Dialektikē tōn agathōn), which puts emphasis on the descent to the specific good, which is appropriate to and cognate with each individual, be that a person, praxis, science or craft. It is also suggested that this might be relevant to Aristotle’s tendency to establish a separation of phronēsis, i.e., practical wisdom, from sophia, i.e., wisdom, in the Nicomachean Ethics.